Ecological restoration for biodiversity conservation triggers response of bark beetle pests and their natural predators. (1st June 2020) - Hekkala, Anne-Maarit; Kärvemo, Simon; Versluijs, Martijn; Weslien, Jan; Björkman, Christer; Löfroth, Therese; Hjältén, Joakim
Abstract: The restoration of forest structure and function is increasingly being used in boreal forests in order to halt the loss of biodiversity. Often ecological restoration is aimed at increasing the volume of dead and dying trees to enhance the biodiversity of deadwood-dependent organisms, but it may also increase population sizes of pest bark beetle species, even several years following restoration. Herein, we used a large-scale restoration experiment in Northern Sweden to assess the 5 years post-restoration effects of restorative gap cutting and prescribed burning on the populations of a set of economically harmful pest bark beetles ( Ips typographus, Polygraphus poligraphus, Tomicus piniperda and Pityogenes chalcographus ) and the most important predators of bark beetles, Thanasimus spp. In addition, we assessed the effects of forest stand characteristics at stand and landscape scale on the abundance of I. typographus . Five years post-restoration, gap-cut stands supported the highest abundances of P. poligraphus and contained the highest count of spruce trees newly attacked by bark beetles. By contrast, prescribed burning generally sustained the lowest abundances of pest bark beetles, especially I. typographus and P. poligraphus, and the highest abundance of their natural predators Thanasimus spp. The population abundance of I. typographus was also positively affected by the area of clear cuts within a 500 m radius from the stand. In conclusion, prescribed burning appears to be a safer method for ecological restoration than gap cutting in the long-term. According to our results, a risk of a local bark beetle outbreak still remains 5 years following the initiation of ecological restoration treatments on spruce-dominated mature gap-cut stands.